Lactobacillus plantarum and propionic acid improve the fermentation quality of high-moisture amaranth silage by altering the microbial community composition - Zhao, Muqier; Wang, Zhijun; Du, Shuai; Sun, Lin; Bao, Jian; Hao, Junfeng; Ge, Gentu (Frontiers in Microbiology, 2022)
Objective The objective of this study was to determine the effect of Lactobacillus plantarum (L. plantarum) and propionic acid (PA) on the microbial community and fermentation performance of high-moisture amaranth silage. Methods Amaranth silages were rown without addition (AhGCK) as a control and with L. plantarum JYLP-002 (AhGLP) or propionic acid (AhGPA) and then were opened after 60 days of ensiling to determine the microbial community and fermentation quality. Results Crude protein (CP) content, lactic acid (LA) content, and lactic acid bacteria (LAB) counts were significantly higher in AhGLP and AhGPA compared with those in AhGCK (p < 0.05). In contrast, pH, acetic acid (AA) content, and yeast and aerobic bacteria counts were significantly lower in AhGLP and AhGPA compared with those in AhGCK (p < 0.05). In addition, propionic acid (PA) levels were markedly higher in AhGPA (p < 0.05). In terms of microbial communities, the silage in the additive groups showed an increased relative abundance of Lactiplantibacillus plantarum and Lentilactobacillus buchneri and a reduced relative abundance of Enterobacter cloacae and Clostridium tyrobutyricum. The abundance of Xanthomonas oryzae was significantly increased in AhGPA, but completely inhibited in the silage supplemented with L. plantarum. Spearman’s correlation analysis revealed that Lentilactobacillus buchneri and Levilactobacillus brevis were positively associated with LA and negatively associated with pH. Conversely, Clostridium tyrobutyricum and Enterobacter cloacae were negatively associated with LA, but positively associated with pH and AA content. AA content was inversely correlated with Lentilactobacillus buchneri. Functional prediction analysis showed that LAB dominated the three groups of silage and the silages containing additives had improved carbohydrate and amino acid metabolism compared with the control silage; in particular, the AhGLP group had more heterotypic fermentation processes and a richer metabolic pathway. Furthermore, the epiphytic Lactiplantibacillus plantarum and Lentilactobacillus buchneri could inhibit the reproductive activity of undesirable microorganisms to a certain extent, thus slowing the spoilage process of the silage. Conclusion In conclusion, L. plantarum can improve fermentation characteristics by modulating the microbial community attached to high-moisture amaranth silage and will prove useful for preserving high-moisture silage.